Kailash Mansarovar a journey to eternity - Khaitan, Chittaranjan K.; Khaitan, Vanita (New Delhi OM Books International, 2007)
Nepal route Pilgrims to Kilash Mansarovar.
Keywords: Tibet Autonomous Region (China) -- Description and travel; Kailash, Mount (Tibet) -- Description and travel; Kailash, Mount (Tibet) -- Pictorial works; Mansarovar, River (Tibet) -- Description and travel; Mansarovar, River (Tibet) -- Pictorial works